(untitled) (Contemporary Mathematics, 2025)
The present paper offers a systematic study of the dispersive concatenation model, with special emphasis on the Kerr law nonlinearity that governs the optical interactions of photons in optical fibers. The model is studied in the environment of multiplicative white noise via the use of Itô Calculus, a stochastic method that significantly impacts the system’s dynamics. To deal with the resulting complexities generated both in the form of the noise and the nonlinear dispersion, the F-expansion method is used to find the solutions of the governing equations. The strong mathematical background enables the successful identification of a wide range of optical soliton solutions, while special emphasis is given to their stability and their conditions of propagation in such environments.